Effects of Varied Soil Leveling Methods on Physical Properties: A Comparative Analysis - Sabahy, Amr; EL-Sheshny, Abdel-Rahman A.; Elsamra, Essam A.; Eid, Mohamed M. M.; Essam, Mohamed (Salehan Institute of Higher Education, 2024)
The total cultivated land area in this context is 8,664,000 square meters, which constitutes about 4% of Egypt's territory. The cultivation relies on old land dams, lines, and furrow surface irrigation systems. A significant portion (76%) of the cultivated land is irrigated with high-density leveled soil instead of unlevelled soil. Leveled soil has very low clay and organic matter content. Land leveling is a preparation or modification process that provides a suitable surface for seeding production. It involves reducing high areas and raising low or deep spots to create a more even surface. Laser-controlled land leveling is a technique that helps create a more even surface by reducing high areas and raising low spots. This process aims to eliminate surface irregularities and create a level plane, which can significantly impact crop germination, uniformity, and, ultimately, the yield of field crops. Laser technology allows for precision in land leveling, ensuring a more consistent seed depth, better water distribution, and improved crop-growing conditions. By creating a more uniform surface, the potential for more consistent crop growth, better water retention, and improved distribution of nutrients is increased. The study's main objective appears to be to determine the most appropriate types of land leveling that can be implemented and to analyze how land leveling treatments affect the physical properties of the soil during different seasons. The data shows that the leaser treatment decreased soil porosity in both seasons, dropping values from 57.36% to 54.34% in the first season and from 55.47% to 51.32% in the second season. In contrast, the